Peningkatan Prestasi Belajar Pelajaran Bahasa Indonesia Menggunakan Media Peta Konsep Peserta Didik Kelas II di MIS Tanjungsari Tersono - Platinda Saptani Mutiarti; Kharisma Pratidina (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
There were problems found in the learning process that took place at MIS Tanjungsari Tersono, Tersono District, Batang Regency. This is indicated by the low results of Indonesian language learning in class II. The low results of Indonesian language learning can be seen from the achievement of student learning outcomes in Indonesian language learning which has not met the school's Minimum Completion Criteria (KKM), which is 70 and the average value is still very low. The purpose of this improvement is This research was carried out with the following objectives: Improving Indonesian language learning outcomes in class II using concept map media at MIS Tanjungsari Tersono, Batang Regency. For implementation, Cycle I to Cycle II were used. The author draws a conclusion, with Concept Map Media there is a significant increase in learning outcomes, as evidenced by an average of 63.5 in the Pre-Cycle or a percentage of learning completion of 40% in Cycle I with a percentage of learning completion of 70% and a significant increase in Cycle II with an average of 77 with a percentage of completion of 90% at MIS Tanjungsari Tersono, Batang Regency.